2022
DOI: 10.14710/jphtcr.v5i2.13758
|View full text |Cite
|
Sign up to set email alerts
|

Family Vulnerability and Children’ Nutritional Status during COVID-19 Pandemic

Abstract: Introduction: COVID-19 infected millions of people and became the main mortality worldwide. COVID-19 also affected other health problems, including nutritional problems. This study aimed to find the factors that affected the nutritional and socio-economic status during the COVID-19 pandemic in a neighborhood of DKI Jakarta.Methods: This study utilized a cross-sectional design. Total sampling method on all families who had children in the 9th Neighborhood, Cawang Sub-District, DKI Jakarta was used. A total of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Demikian juga di Indonesia, hasil penelitian Syafiq et al, (2022) bahwa rumah tangga dengan pendapatan lebih rendah akibat pandemik bersiko 4 kali mengalami rawan pangan dibandingkan rumah tangga dengan pendapatan yang lebih tinggi. Penelitian (Yusuf et al, 2022) bahwa pandemik menyebabkan masyarakat kehilangan pekerjaan dan menyebabkan masyarakan lebih berisiko mengalami kekurangan gizi.…”
Section: Pembahasan 1 Ketahanan Panganunclassified
“…Demikian juga di Indonesia, hasil penelitian Syafiq et al, (2022) bahwa rumah tangga dengan pendapatan lebih rendah akibat pandemik bersiko 4 kali mengalami rawan pangan dibandingkan rumah tangga dengan pendapatan yang lebih tinggi. Penelitian (Yusuf et al, 2022) bahwa pandemik menyebabkan masyarakat kehilangan pekerjaan dan menyebabkan masyarakan lebih berisiko mengalami kekurangan gizi.…”
Section: Pembahasan 1 Ketahanan Panganunclassified
“…Surni et al (2021) found that thousands of employees in Indonesia experienced termination of employment when the COVID-19 pandemic hit. This incident worsened the community's economic situation and increased the poverty rate to 27.55 million people annually in 2020 (Yusuf et al, 2022). The government alleviated poverty during the pandemic by providing social assistance, direct cash assistance, and community economic empowerment programs (Setyari & Purwanti, 2022).…”
Section: Introductionmentioning
confidence: 99%